Influência cultural pomerana: permanências e adaptações na arquitetura produzida pelos fundadores da Comunidade Palmeira, Cerrito Alegre, terceiro distrito de Pelotas (RS) - Bosenbecker, Vanessa Patzlaff (2012)
The study approaches the architecture produced by the Pomeranian immigrants in Osório and PyCrespo colonies, in Cerrito Alegre, Third District of Pelotas, Rio Grande do Sul. They are the third generation of Pomeranians in Brazil. The studied sites belong to the founders group of Palmeira community, a free Lutheran religious association of that locality. The main objective of this research is to identify the continuities and changes in t he construction mode and functions organization in their properties. To reach the objective, sites and residences functions organization characteristics, as well as the construction techniques used by the analyzed group, were compared with the data brought by the historiography concerned with the architecture produced by the Pomeranians in their homeland and by the Pomeranian immigrants in Rio Grande do Sul, as well as with some other architectures produced by immigrants of other ethnicities. Thus, the obtained data in the sites survey were related to the specialized reference literature (WEIMER, 2005; BERTUSSI, 1987 and; MACEDO, 1987), in order to identify continuities, adjustments and ruptures in the architecture produced by the Pomeranian immigrants grandsons